Germinación y crecimiento inicial de Ocotea aciplylla "canela moena" con diferentes sustratos en el laboratorio de adaptación y producción de plantas del CIEFOR- Puerto Almendra Loreto-Perú, 2020 - Oyarce Salas, Pedro Raul (2021)
The present study was carried out at the CIEFOR Puerto Almendra FCF - UNAP, San Juan Bautista, Maynas, Loreto. Objective, to determine the increase in height and diameter; survival and quality of 200 seeds of Ocotea aciphylla in a nursery with different substrates. The planting beds were prepared at ground level, with material from the area; The simple randomized experimental design with 8 treatments and 25 repetitions was used. The greatest increase in height was recorded by the CF treatment (black earth (20%) + chicken manure (50%) + rotten stick (30%) with pre-germination treatment) with 32.2 cm; while the greatest increase in diameter is reported by the BF treatment (black earth (50%) + chicken manure (30%) + rotten stick (20%) + pre-germination treatment) with 0.28 mm. Seedlings of Ocotea aciphylla “cinnamon moena” registered results between 70% and 96% of survival for the treatments and the highest amount of survival with 24 live plants (96%) was found at treatment AF (alluvial sand + Pre-germination treatment). Use substrates that correspond to the CF treatment (black earth (20%) + chicken manure (50%) + rotten stick (30%) and with pre-germination treatment) and to the BF treatment (black earth (50%) + chicken manure (30%) + rotten stick (20%) with pre-germination treatment) for achieving the best results in the experiment.